INVESTIGATION OF THE OPTICAL BONE DENSITY OF THE ALVEOLAR PROCESSES IN THE AREA OF DEFECTS OF DENTITION - S.A. German (Український стоматологічний альманах, 2018)
Special non-invasive methods of investigating the condition of bone tissue have been developed and introduced into clinical practice in recent decades, allowing with high accuracy to detect changes of optical density of bone tissue of the alveolar process of the jaws. Accurate determination of bone density of the alveolar bone is of paramount importance for diagnosis, treatment planning and dental procedures in periodontal disease, osteoporosis, osteointegrated implants were used.